Toward a Grammar of Passages - Coe, Richard M. (Book collections on Project MUSE., 1987)
"The mature writer is recognized ... by his ability to create a flow of sentences, a pattern of thought that is produced, one suspects, according to the principles of yet another kind of grammar-a grammar, let us say, of passages."--Mina Shaughnessy Richard M. Coe has developed such a "grammar," one which uses a simple graphic instrument to analyze the meaningful relationships between sentences in a passage and to clarify the function of structure in discourse. Working in the tradition of Christensen's generative rhetoric, Coe presents a two-dimensional graphic matrix that effectively analyze.